Symposium 1: Networking educational administrators through e-Teaching - Power, Michael; Lapointe, Claire (Proceedings of the International Conference on Networked Learning, 2018)
This paper is about e-teaching in the context of a university graduate program and how the program metamorphosed from being entirely campus based to entirely online, and from declining enrolments to increasing enrolments. It is about the faculty and lecturers who conducted a critical analysis of their particular situation, examined their options, researched other program delivery options and finally settled on a solution that has proven successful. Because of this labour-intensive process, they discovered that the networking processes undertaken by them to complete their mandate enabled them to become better networking mentors as e-teachers. This is their story and it sheds a critical light on various delivery models currently deployed by universities worldwide. Most importantly, it demonstrates that a good deal of reflection and agreement on what good teaching is and how it can be achieved has to be conducted prior to delivery model adoption. It also raises the question as to the wisdom of across-the-board institutionally decided program delivery choices. Such choices not only affect e-learners down the road but also directly affect faculty’s motivation and ability, as a community of practice, to carry out their teaching responsibilities efficiently and sustainably. Data was gleaned from an ongoing study, mostly from a series of semi-structured interviews with administrators and faculty, including lecturers, who participated, over the course of a two-year period, in transferring this program from on-campus to online. Six semi-structured interviews, each lasting between 60 and 90 minutes, were conducted. Access to work documents, ongoing email exchanges and personal conversations completed the data set. The interview guide used was developed to highlight respondent experience over the course of the two-year program migration online, focusing on the move from on-campus teaching to e-teaching, course delivery model selection, and an open questions for respondents to add related comments. Complete data analysis and interpretation is proceeding as this proposal is being sent to conference organisers. Results show a high degree of unanimity in the decision to adopt BOLD as program delivery mechanism. Respondents describe how it gave them back what they most liked in their work: direct and continuous, regular contact with their students, free-flowing discussions on concepts, principles and their applications, access to students who would normally not enrol in their courses and a workload that was more manageable than other delivery systems they had known.